Knowledge, Trust or Perspectives? A Causal Mediation Analysis of How a Citizens' Jury Affected Voting Intentions in the General Public - Christensen Henrik Serup; Leino Mikko; Setälä Maija; Strandberg Kim (WILEY, 2022)
Previous studies suggest that information from deliberative mini-publics helps voters make informed and reflected judgements and act accordingly. Despite a growing body of literature, the causal mechanisms remain unclear. This study examines three causal mechanisms for affecting voting intentions in a referendum: 1) factual knowledge, 2) trusted information proxy, or 3) perspective-taking of the opinions of others. The data come from a referendum on a municipal merger in Korsholm, Finland. In a field experiment, a statement from a citizens' jury on the merger was released to a treatment group and differences in opinions and voting intentions were compared with a control group that did not receive the statement. Causal mediation analysis examines which of the three causal mechanisms best explains how the jury's statement affected intended voting behaviour. We find that reading the statement increased factual knowledge, trust, and perspective-taking, but only increased factual knowledge affected voting intentions.